Analysis of factors affecting differences in potassium buffering capacity in several soil orders - Fajarini, Permata Harty Noor; Hanudin, Eko; Purwanto, Benito Heru (Jurnal Ilmu Pertanian, 2025)
Each soil order has different reactivity to potassium ion retention capacity, especially potassium buffering capacity. These differences are related to soil characteristics, including clay mineral content and type, cation exchange capacity, and soil texture class. This study compared the potassium buffering capacity (PBCk) of Andisols, Alfisols, Inceptisols, and Vertisols. The PBCk experiment reacted 2.5 grams of air-dried soil (passing a 0.5 mm sieve) and 25 ml of KCl solution with a series of concentrations of 0, 25, 50, 75, 125, 150, 175, 200, 225, and 250 ppm. Then, it was shaken for 24 hours to reach equilibrium conditions. The next day, the solution was centrifuged to obtain a clear solution. The remaining K content in the equilibrium solution was measured using a flame photometer. The amount of K read was calculated to obtain the Q/I factor and PBCk value from the gapon equation. The Q/I relationship was used to estimate PBCk values for each soil order with changes in K in the solution or Q (∆K) as the X axis and the intensity of K or I (CRk) as the Y axis. Then, the K intensity data were connected to the PBCk results to determine the buffer capacity of the four soil orders. Vertisols showed the highest PBCk (1.099 cmol kg-1/mol L-1)0.5, followed by Andisols, Alfisols, and Inceptisols. The determining factors include clay minerals in the form of smectite (2:1), high CEC value, and soil texture dominated by clay.